Redefining ethical leadership in a 21st-century healthcare system. Issue 1 (January 2016) - Ho, Anita; Pinney, Stephen
Traditional ethical leadership in healthcare concentrated on the oversight of the individual provider–patient relationship. However, as care delivery becomes predominantly team-based and integrated across provider organizations, these ethical frameworks also need to consider meso- and macro-factors within the system. These broader issues require managers and administrative leaders to augment their ethical perspectives beyond current and prospective patients with those of the team, organization, and broader system, where high levels of coordination and oversight are essential. Administrators are increasingly ethically accountable not only for how individual care encounters are conducted (micro level) but also for how the system is organized to deliver and ensure quality care for patients receiving care (meso level) and service populations who turn to them for care when needed (macro level).